Seroprevalence and risk factors of hantavirus and hepatitis E virus exposure among wildlife farmers in Vietnam - Ha Thi Thanh Nguyen; Hu Suk Lee; Bernard Bett; Jiaxin Ling; Thang Nguyen-Tien; Sinh Dang-Xuan; Hung Nguyen-Viet; Fred Unger; Steven Lam; Vuong Nghia Bui; Tung Duy Dao; Åke Lundkvist; et al. (PLoS ONE, 2025)
Background Wildlife farming is a growing industry, but it poses substantial risks for zoonotic disease transmission, including infections caused by hantaviruses and hepatitis E virus (HEV). This study aimed to determine seroprevalences of these viruses among wildlife farmers and identify associated risk factors. Methods A cross-sectional study was conducted among 210 wildlife farmers in Lao Cai and Dong Nai provinces in Vietnam who raised bats, bamboo rats, civets, and wild boars. Of these, 207 provided serum samples for serological testing for hantavirus and HEV antibodies. Apparent (AP) and true (TP) prevalences were estimated, and multivariable logistic regression was performed to identify risk factors. Results The AP of hantavirus IgG was 8.7%, 95% confidence interval (CI): 5.4–13.6 (TP: 4.7%, 95% credible interval (CrI): 0.2–11.1). HEV IgG AP was 26.7%, 95%CI: 20.8–33.2 (TP: 27.1%, 95%CrI: 21.3–33.4). Hantavirus IgM testing was also performed due to higher IgG seroprevalence compared to earlier studies, detecting IgM antibodies in 1.9% of samples (95%CI: 0.6–5.2) (TP: 1.7%, 95%CrI: 0.1–4.7). Hantavirus seropositivity was significantly associated with engaging only in wildlife farming, and not participating in other activities such as hunting, trading, slaughtering, processing, guano collection, or consumption (OR = 2.7, 95% CI: 1.1–6.9). HEV seropositivity was significantly associated with men gender (OR = 3.1, 95%CI: 1.4–7.3), older age (OR = 1.03, 95%CI: 1.0–1.1), raw meat consumption (OR = 6.8, 95%CI: 1.6–31.8), residing at higher altitudes (OR = 31.6, 95%CI: 5.5–204.4), and reporting use of protective clothing (OR = 4.0, 95%CI: 1.4–11.2), although their proper use was not assessed. Conclusions This study highlights behavioural and environmental risk factors associated with wildlife farming and zoonotic pathogens exposure. Public health interventions should focus on biosecurity, proper hygiene practices, and risk communication to reduce the transmission in wildlife farming settings.